2015
DOI: 10.3748/wjg.v21.i22.6835
|View full text |Cite
|
Sign up to set email alerts
|

Predictive roles of intraoperative blood glucose for post-transplant outcomes in liver transplantation

Abstract: Diabetogenic traits in patients undergoing liver transplantation (LT) are exacerbated intraoperatively by exogenous causes, such as surgical stress, steroids, blood transfusions, and catecholamines, which lead to intraoperative hyperglycemia. In contrast to the strict glucose control performed in the intensive care unit, no systematic protocol has been developed for glucose management during LT. Intraoperative blood glucose concentrations typically exceed 200 mg/dL in LT, and extreme hyperglycemia (> 300 mg/dL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 70 publications
0
16
0
4
Order By: Relevance
“…The routine provision of abundant anesthesia resources for liver transplantation allowed for frequent glucose monitoring and rapid intervention for changes in plasma glucose when detected and may enhance safety for aggressive glucose management in this patient population. Patients undergoing liver transplant have the potential to exhibit hyperglycemia due to insulin resistance [9] and the exogenous administration of steroids may make hypoglycemia less likely; it appears that aggressive insulin therapy is not associated with a greater risk of hypoglycemia compared to conventional control and can be managed safely during the intraoperative phase of liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The routine provision of abundant anesthesia resources for liver transplantation allowed for frequent glucose monitoring and rapid intervention for changes in plasma glucose when detected and may enhance safety for aggressive glucose management in this patient population. Patients undergoing liver transplant have the potential to exhibit hyperglycemia due to insulin resistance [9] and the exogenous administration of steroids may make hypoglycemia less likely; it appears that aggressive insulin therapy is not associated with a greater risk of hypoglycemia compared to conventional control and can be managed safely during the intraoperative phase of liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients presenting for liver transplantation frequently display insulin resistance, termed hepatogenous diabetes [8,9]. In addition, surgical stress, steroids, transfusion and the onset of gluconeogenesis after reperfusion of the new graft result in glucose instability.…”
Section: Introductionmentioning
confidence: 99%
“…Atchison et al reported on the blood glucose trends in patients during orthotopic liver transplantation, and noted that the blood glucose concentrations typically increased from 110 ± 46 to 204 ± 60 mg/dL in the preanhepatic phase, followed by a further increase to 384 ± 72 mg/dL during the neohepatic phase . Park reported on the blood glucose trends from the day before surgery to posttransplant day 30 in patients with LDLT ( n = 210) and noted that patients who underwent LDLT showed similar intraoperative blood glucose trends . With regard to the postoperative course, the blood glucose level abruptly decreased two days after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid increase in blood glucose concentration (BGC) after graft reperfusion is one of them and results from the systemic influx of glucose from hepatocytes destroyed by ischemia reperfusion injury 2 , 3 . Intraoperative hyperglycemia during liver transplantation is associated with surgical site infection, overall infectious complications, and mortality 4 6 . The decrease in immunity 7 , 8 and increase in ischemia reperfusion injury 9 resulting from acute hyperglycemic disturbance are thought to be the underlying mechanisms for these adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, hyperglycemia is still not rare because the extent of hepatocyte ischemia reperfusion injury is profound and insulin sensitivity is impaired due to underlying chronic liver disease, surgical stress, vasoactive drugs, and steroid immunosuppression. The optimal postreperfusion glycemic strategies to improve liver transplant outcomes remain unresolved 6 .…”
Section: Introductionmentioning
confidence: 99%